Super-thick composite coating with multi-layer structure and preparation method of super-thick composite coating
The multi-layer ultra-thick composite coating solves the problems of thin thickness and low bonding strength of traditional coatings, achieves improved wear resistance, friction reduction and corrosion resistance, and is suitable for metal moving parts in harsh environments.
Patent Information
- Application Number
- CN202510960312.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-11
- Publication Date
- 2025-10-10
AI Technical Summary
Traditional coatings are thin and have large internal stresses, resulting in insufficient wear resistance, friction reduction and corrosion resistance, making it difficult to meet long-term service requirements. In addition, the coating has low bonding strength and is prone to through-pores that allow chloride ions to penetrate.
An ultra-thick composite coating with a multi-layer structure, including a substrate, a bonding layer, a transition layer and a surface layer, is deposited by magnetron sputtering or arc ion plating technology to deposit alternating layers of CrN/CrCN, AlCrTiNiCN/CrNiCN and a Ni-CrC-DLC surface layer to reduce internal stress and avoid through-pores.
The coating thickness exceeds 20 microns, effectively blocking chloride ions from entering the substrate, improving corrosion resistance and friction and wear performance, making it suitable for metal moving parts in harsh environments and extending service life.
Smart Images

Figure CN120758837A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ultra-thick composite coatings, and in particular to an ultra-thick composite coating with a multi-layer structure and a preparation method thereof. Background Art
[0002] As the national strategy advances from shallow sea to deep sea, the wear and corrosion problems of equipment such as helicopters in marine environments are becoming increasingly prominent. The demand for improving the wear resistance of key components such as metal parts is becoming more and more urgent. Metal parts such as 30CrMnSi have high strength and toughness and are widely used in marine equipment such as helicopters. However, metal parts have poor wear and corrosion resistance, resulting in severe wear and corrosion in marine atmospheric environments with high humidity, high salt fog, strong winds and strong ultraviolet rays.
[0003] Carbon-based coatings prepared by physical vapor deposition methods have attracted a lot of attention due to their excellent tribological properties and chemical inertness. Some people have prepared silicon-doped carbon-based coatings. Due to their dense coating structure, they prevent chloride ion attack and have good corrosion resistance. Some researchers believe that the dopant changes the passivation behavior of the carbon-based coating by forming inert oxide compounds on the surface, thereby improving the corrosion resistance. However, due to the presence of internal stress during the coating deposition process, the thickness of these coatings is relatively thin, generally around 2 to 5 μm, making it difficult for their excellent friction reduction and wear resistance to meet the needs of long-term service, and the load-bearing capacity is also greatly restricted. At the same time, the interface structure of traditional amorphous carbon-based films is single, and the bonding force of their single-layer or double-layer structures is relatively low. It is difficult to maintain a low wear rate under high shear stress, and the simple single-layer and double-layer structures cannot effectively avoid the through-pores inside the coating, resulting in chloride ions being able to easily penetrate the coating and contact the substrate, which cannot play a good role in corrosion resistance, thereby greatly reducing the service life of the coating. Ultra-thick coatings have been less studied due to the difficulty of preparation and low deposition efficiency.
[0004] Therefore, developing a coating that has both good wear resistance and friction reduction properties and good corrosion resistance is an important way to solve the above problems. Summary of the Invention
[0005] In order to overcome the problem that the thickness of these coatings is relatively thin due to the existence of internal stress in the traditional coating deposition process, their excellent anti-friction and wear-resistant properties cannot meet the needs of long-term service, and their load-bearing capacity is also greatly restricted.
[0006] The technical solution of the present invention is: a multi-layer ultra-thick composite coating, including a substrate, a bonding layer, a transition layer, an alternating laminate and a surface layer; the outer surface of the substrate is provided with a bonding layer composed of a Cr layer, the outer surface of the bonding layer is provided with a transition layer composed of a CrN / CrCN double layer, the outer surface of the transition layer is provided with an alternating laminate composed of alternately deposited AlCrTiNiCN / CrNiCN, and the outer surface of the alternating laminate is provided with a surface layer composed of Ni-CrC-DLC.
[0007] Preferably, the internal stress of the coating is effectively reduced by the deposition of bonding layers, transition layers and alternating layers, so that the coating thickness can reach more than 20 microns, and the ultra-thick multi-layer structure can effectively avoid through-pores inside the coating, effectively blocking chloride ions from penetrating the coating into the substrate, playing a good role in corrosion resistance, thereby greatly increasing the service life of the coating.
[0008] Preferably, the thickness of the bonding layer is 0.2 to 2 μm; the thickness of the transition layer is 0.5 to 5 μm; the thickness of the alternating laminate is 2 to 30 μm; the alternating laminate comprises two or more alternating laminate periodic layers, wherein each alternating laminate periodic layer comprises a layer of AlCrTiNiCN and a layer of CrNiCN; the thickness of the surface layer is 0.5 to 5 μm; and the total thickness of the multi-layer structure ultra-thick composite coating is 4 to 40 μm.
[0009] Preferably, the ultra-thick composite coating can be used in the field of surface protection of metal moving parts in harsh environments.
[0010] A method for preparing a multi-layer ultra-thick composite coating includes the multi-layer ultra-thick composite coating described above, using magnetron sputtering technology and ion source assisted magnetron sputtering technology to deposit alternating layers and surface layers on the surface of the bonding layer and the transition layer to form a multi-layer ultra-thick composite coating.
[0011] The specific steps are as follows:
[0012] Step 1: Pre-cleaning of workpiece:
[0013] After grinding and polishing, the workpiece surface is ultrasonically placed in anhydrous alcohol solution for 10 to 20 minutes, then dried with hot air and placed on the workpiece rack in the vacuum chamber to wait for coating;
[0014] Step 2: Cr bonding layer:
[0015] A high-purity chromium target is used, an inert gas is used as the working atmosphere, and magnetron sputtering technology is used to deposit a bonding layer on the substrate surface. The bias voltage is -20 to -100 V, the target power is 2 to 8 kW, the vacuum chamber pressure is 0.3 to 1.0 Pa, the deposition temperature is 100 to 350°C, and the deposition time is 10 to 90 minutes.
[0016] Step 3: Plating CrN / CrCN transition layer:
[0017] A Cr target is used as a target material and N2 gas is used as a working gas. A magnetron sputtering technology is used to deposit a CrN layer on the surface of the bonding layer. The bias voltage is -20 to -150 V, the target power is 2 to 8 kW, the vacuum chamber pressure is 0.3 to 1.0 Pa, the deposition temperature is 100 to 350° C., and the deposition time is 20 to 100 minutes. A mixed gas of inert gas, N2 gas and carbon source gas is then introduced. The vacuum chamber pressure is 0.3 to 1.0 Pa, the bias voltage is -20 to -150 V, the target power is 2 to 8 kW, the deposition temperature is 100 to 350° C., and the deposition time is 20 to 100 minutes.
[0018] Step 4: Plating AlCrTiNiCN / CrNiCN alternating layers:
[0019] Using AlCrTiNi target and CrNi target as target materials, N2 gas and carbon-containing gas source as working gas, and inert gas as auxiliary gas, magnetron sputtering technology is used to alternately deposit AlCrTiNiCN layers and CrNiCN layers on the surface of the transition layer, wherein the bias voltage is -20 to -150 V, the target power is 2 to 8 kW, the vacuum chamber pressure is 0.3 to 1.0 Pa, the deposition temperature is 100 to 350°C, and the deposition time is 30 to 360 minutes;
[0020] Step 5: Ni-CrC-DLC surface coating:
[0021] Cr target and Ni target are used as target materials, carbon-containing gas source is used as working gas, inert gas is used as auxiliary gas, magnetron sputtering technology is adopted, and the ion source is turned on at the same time. The vacuum chamber pressure is 0.3~1.0Pa, the bias voltage is -20~-150V, the target power is 2~8kW, the deposition temperature is 100~350℃, and the deposition time is 20~100min.
[0022] A method for preparing a multi-layer ultra-thick composite coating includes the multi-layer ultra-thick composite coating described above, using arc ion plating technology and ion source assisted arc ion plating technology to deposit alternating layers and surface layers on the surface of the bonding layer and the transition layer to form a multi-layer ultra-thick composite coating.
[0023] The specific steps are as follows:
[0024] Step 1: Pre-cleaning of workpiece:
[0025] After grinding and polishing, the workpiece surface is ultrasonically placed in anhydrous alcohol solution for 10 to 20 minutes, then dried with hot air and placed on the workpiece rack in the vacuum chamber to wait for coating;
[0026] Step 2: Cr bonding layer:
[0027] The adhesive layer is formed by using high-purity chromium target, inert gas as working atmosphere and adopting arc ion plating technology, wherein the bias voltage is -30 to -200V, the target arc current is 80 to 200A, the vacuum chamber pressure is 0.5 to 2.0Pa, the deposition temperature is 100 to 350℃, and the deposition time is 5 to 50min;
[0028] Step three: plating CrN / CrCN transition layer
[0029] The CrN layer is deposited on the adhesive layer by using Cr target as target material, N2 gas as working gas and adopting arc ion plating technology, wherein the bias voltage is -40 to -200V, the target arc current is 80 to 200A, the vacuum chamber pressure is 1.0 to 3.0Pa, the deposition temperature is 100 to 350℃, and the deposition time is 10 to 50min; then the mixed gas of inert gas, N2 gas and carbon source gas is introduced, the vacuum chamber pressure is 1.0 to 3.0Pa, the bias voltage is -40 to -200V, the target arc current is 80 to 200A, the deposition temperature is 100 to 350℃, and the deposition time is 10 to 50min;
[0030] Step four: plating AlCrTiNiCN / CrNiCN alternating stack
[0031] The AlCrTiNiCN layer and CrNiCN layer are deposited on the transition layer by using AlCrTiNi target and CrNi target as target material, N2 gas and carbon-containing gas source as working gas, inert gas as auxiliary gas and adopting arc ion plating technology, wherein the bias voltage is -40 to -200V, the target arc current is 80 to 200A, the vacuum chamber pressure is 1.0 to 3.0Pa, the bias voltage is -40 to -300V, the deposition temperature is 100 to 350℃, and the deposition time is 20 to 240min;
[0032] Step five: plating Ni-CrC-DLC surface layer
[0033] The Ni-CrC-DLC surface layer is plated by using Cr and Ni target as target material, carbon-containing gas source as working gas, inert gas as auxiliary gas, adopting arc ion plating technology and simultaneously opening the ion source, wherein the vacuum chamber pressure is 1.0 to 3.0Pa, the bias voltage is -40 to -300V, the target arc current is 80 to 200A, the deposition temperature is 100 to 350℃, and the deposition time is 10 to 50min.
[0034] Preferably, the carbon source gas includes C2H2 and / or CH4; the inert gas atmosphere includes Ar atmosphere.
[0035] The present application has the following advantages:
[0036] 1. Through the deposition of bonding layer, transition layer and alternating lamination, the internal stress of the coating is effectively reduced, so that the coating thickness can reach more than 20 microns. The ultra-thick multi-layer structure can effectively avoid through-pores inside the coating, effectively blocking chloride ions from penetrating the coating into the substrate, playing a good role in corrosion resistance, thereby greatly increasing the service life of the coating;
[0037] 2. The multi-layered ultra-thick composite coating prepared by the present invention not only has excellent mechanical properties and friction and wear properties, but also has good corrosion protection performance. It can be applied to moving parts that require long life and wear resistance and corrosion resistance, and can also be used in low-temperature environments of -100°C.
[0038] 3. The present invention can not only adopt the arc ion plating and ion source assisted arc ion plating technologies that are widely used in industry to prepare ultra-thick composite coatings, but also adopt magnetron sputtering and ion source assisted magnetron sputtering technologies to prepare ultra-thick composite coatings. Different preparation technologies can be selected according to different technical characteristics, which has certain flexibility and is easier to promote and apply. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 Shown is a schematic diagram of the three-dimensional structure of the multi-layer ultra-thick composite coating of the present invention;
[0040] Figure 2 Shown is a schematic cross-sectional structure diagram of a multi-layer ultra-thick composite coating of the present invention;
[0041] Figure 3 Shown is a friction coefficient curve of the multi-layered ultra-thick composite coating in Example 1 of the present invention.
[0042] Explanation of the reference numerals: 1. substrate; 2. bonding layer; 3. transition layer; 4. alternating layers; 5. surface layer. DETAILED DESCRIPTION
[0043] The present invention will be further described below with reference to the accompanying drawings and examples.
[0044] Example 1
[0045] In this embodiment, the ultra-thick composite coating with the multi-layer structure is prepared on the surface of a 316 stainless steel sample. The specific process steps are as follows:
[0046] Step 1: Pre-cleaning of workpiece:
[0047] After grinding and polishing, the workpiece / sample surface is ultrasonicated in anhydrous alcohol solution for 20 minutes, then blown dry with dry nitrogen and placed on the workpiece holder in the vacuum chamber to wait for coating;
[0048] Step 2: Ion etching and cleaning:
[0049] The sample treated in step 1 was placed in the vacuum chamber of the magnetron sputtering coating machine and evacuated to a vacuum better than 5×10 - 3 Pa; turn on the ion source, introduce high-purity argon gas, adjust the gas pressure to 0.3 Pa, apply a negative bias voltage to the substrate 1, and etch and clean the substrate 1 at a bias voltage of -200 V to remove impurities such as oxides and contamination layers attached to the surface. The etching time is 30 minutes;
[0050] Step 3: Deposition of Cr bonding layer 2:
[0051] A high-purity chromium target with a purity of 99.9% was used. After the ion etching was completed, the argon gas pressure was adjusted to 0.4 Pa. The magnetron sputtering chromium target was turned on to deposit the bonding layer 2 on the surface of the substrate 1. The bias voltage was -60 V, the target power was 4 kW, the deposition temperature was 200°C, and the deposition time was 30 min.
[0052] Step 4: Deposition of CrN / CrCN double-layer transition layer 3:
[0053] N2 gas was introduced, and the flow rate ratio of argon gas to nitrogen gas was adjusted to 1:4. The pressure of the vacuum chamber was adjusted to 0.5 Pa. The bias voltage and target power remained unchanged. A CrN layer was deposited on the surface of the bonding layer 2 by magnetron sputtering technology for 30 minutes. Then, C2H2 gas was introduced, and the total flow rate ratio of argon gas to nitrogen gas and C2H2 gas was adjusted to 1:4. The bias voltage and target power remained unchanged. A CrCN layer was deposited on the surface of the CrN layer by magnetron sputtering technology for 30 minutes.
[0054] Step 5: Plating AlCrTiNiCN / CrNiCN alternating layers 4:
[0055] Using AlCrTiNi and CrNi targets as target materials, N2 and C2H2 as working gases, and argon as auxiliary gas, the vacuum chamber pressure was adjusted to 0.6 Pa. Magnetron sputtering technology was used to deposit AlCrTiNiCN and CrNiCN layers on the surface of the transition layer 3. The thickness of the single layer was controlled by adjusting the residence time of the substrate 1 in front of the AlCrTiNi and CrNi targets. The bias voltage was -90 V, the power of the AlCrTiNi target was 3 kW, the power of the CrNi target was 5 kW, the deposition temperature was 230°C, and the deposition time was 180 min.
[0056] Step 6: Ni-CrC-DLC coating 5:
[0057] Cr and Ni targets are used as target materials, carbon-containing gas source is used as working gas, argon is used as auxiliary gas, magnetron sputtering technology is adopted, and the ion source is turned on at the same time. The vacuum chamber pressure is 0.4Pa, the bias voltage is -80V, the target power is 6kW, the deposition temperature is 150℃, and the deposition time is 60min. After the deposition is completed, the sputtering target is turned off, the negative bias voltage of the substrate is stopped, the gas is stopped, and the vacuum is continued. The workpiece is cooled to below 50℃ with the furnace, the vacuum chamber is opened, the workpiece is taken out, and the coating process is completed.
[0058] The total thickness of the obtained multi-layer composite coating is 11.7 microns; the nanohardness is 21 GPa; and the friction coefficient with the GCr15 steel ball is 0.18.
[0059] Example 2
[0060] In this embodiment, the ultra-thick composite coating with the multi-layer structure is prepared on the surface of the TC4 titanium alloy sample. The specific process steps are as follows:
[0061] Step 1: Pre-cleaning of workpiece:
[0062] After grinding and polishing, the workpiece / sample surface is ultrasonically placed in anhydrous alcohol solution for 18 minutes, then blown dry with dry nitrogen and placed on the workpiece holder in the vacuum chamber to wait for coating;
[0063] Step 2: Ion etching and cleaning:
[0064] The sample treated in step 1 was placed in the vacuum chamber of the arc ion plating machine and evacuated to a vacuum better than 5×10 - 3 Pa; turn on the ion source, introduce high-purity argon gas, adjust the gas pressure to 0.35Pa, apply a negative bias voltage to the substrate 1, and etch and clean the substrate 1 at a bias voltage of -200V to remove impurities such as oxides and contamination layers attached to the surface. The etching time is 50min;
[0065] Step 3: Deposition of Cr bonding layer 2:
[0066] A high-purity chromium target with a purity of 99.9% was used. After ion etching was completed, the argon gas pressure was adjusted to 0.5 Pa. The arc chromium target was turned on to deposit the bonding layer 2 on the surface of the substrate 1. The bias voltage was -90 V, the chromium target arc current was 120 A, the deposition temperature was 200°C, and the deposition time was 35 minutes.
[0067] Step 4: Deposition of CrN / CrCN double-layer transition layer 3:
[0068] N2 gas was introduced, and the flow rate ratio of argon gas to nitrogen gas was adjusted to 1:4. The pressure of the vacuum chamber was adjusted to 0.6 Pa. The bias voltage and target power remained unchanged. A CrN layer was deposited on the surface of the bonding layer 2 by arc ion plating technology for 40 minutes. Then, C2H2 gas was introduced, and the total flow rate ratio of argon gas to nitrogen gas and C2H2 gas was adjusted to 1:4. The bias voltage and arc current remained unchanged. A CrCN layer was deposited on the surface of the CrN layer by arc ion plating technology for 60 minutes.
[0069] Step 5: Plating AlCrTiNiCN / CrNiCN alternating layers 4:
[0070] Using AlCrTiNi and CrNi targets as target materials, N2 and C2H2 as working gases, and argon as auxiliary gas, the vacuum chamber pressure was adjusted to 0.4 Pa, and arc ion plating technology was used to deposit AlCrTiNiCN and CrNiCN layers on the surface of the transition layer 3. The thickness of the single layer was controlled by adjusting the residence time of the substrate 1 in front of the AlCrTiNi and CrNi targets. The bias voltage was -90 V, the arc current of the AlCrTiNi target was 120 A, the arc current of the CrNi target was 100 A, the deposition temperature was 160°C, and the deposition time was 240 min.
[0071] Step 6: Ni-CrC-DLC coating 5:
[0072] Cr and Ni targets are used as target materials, carbon-containing gas source is used as working gas, argon is used as auxiliary gas, arc ion plating technology is adopted, the ion source is turned on at the same time, the vacuum chamber pressure is 0.6Pa, the bias voltage is -80V, the arc current of Cr and Ni targets are 120A and 90A respectively, the deposition temperature is 150℃, and the deposition time is 70min. After the deposition is completed, the arc target is turned off, the negative bias of the substrate is stopped, the gas is stopped, and the vacuum is continued. The workpiece is cooled to below 80℃ with the furnace, the vacuum chamber is opened, the workpiece is taken out, and the coating process is completed.
[0073] The total thickness of the obtained multi-layer composite coating is 21.3 microns; the nanohardness is 25 GPa; and the friction coefficient with the GCr15 steel ball is 0.16.
[0074] Example 3
[0075] In this embodiment, the ultra-thick composite coating with the multi-layer structure is prepared on the surface of an 8Cr4Mo4V bearing steel sample. The specific process steps are as follows:
[0076] Step 1: Pre-cleaning of workpiece:
[0077] After grinding and polishing, the workpiece / sample surface is ultrasonicated in anhydrous alcohol solution for 25 minutes, then blown dry with dry nitrogen and placed on the workpiece holder in the vacuum chamber to wait for coating;
[0078] Step 2: Ion etching and cleaning:
[0079] The sample treated in step 1 was placed in the vacuum chamber of the magnetron sputtering coating machine and evacuated to a vacuum better than 5×10 - 3 Pa; turn on the ion source, introduce high-purity argon gas, adjust the gas pressure to 0.45Pa, apply a negative bias voltage to the substrate 1, and etch and clean the substrate 1 at a bias voltage of -200V to remove impurities such as oxides and contamination layers attached to the surface. The etching time is 40min;
[0080] Step 3: Deposition of Cr bonding layer 2:
[0081] A high-purity chromium target with a purity of 99.9% was used. After the ion etching was completed, the argon gas pressure was adjusted to 0.45 Pa. The magnetron sputtering chromium target was turned on to deposit the bonding layer 2 on the surface of the substrate 1. The bias voltage was -100 V, the target power was 7 kW, the deposition temperature was 200°C, and the deposition time was 40 minutes.
[0082] Step 4: Deposition of CrN / CrCN double-layer transition layer 3:
[0083] N2 gas was introduced, and the flow rate ratio of argon gas to nitrogen gas was adjusted to 1:4. The pressure of the vacuum chamber was adjusted to 0.55 Pa. The bias voltage and target power remained unchanged. A CrN layer was deposited on the surface of the bonding layer 2 by magnetron sputtering technology for 50 minutes. Then, C2H2 gas was introduced, and the total flow rate ratio of argon gas to nitrogen gas and C2H2 gas was adjusted to 1:4. The bias voltage and target power remained unchanged. A CrCN layer was deposited on the surface of the CrN layer by magnetron sputtering technology for 60 minutes.
[0084] Step 5: Plating AlCrTiNiCN / CrNiCN alternating layers 4:
[0085] Using AlCrTiNi and CrNi targets as target materials, N2 and C2H2 as working gases, and argon as auxiliary gas, the vacuum chamber pressure was adjusted to 0.45 Pa. Magnetron sputtering technology was used to deposit AlCrTiNiCN and CrNiCN layers on the surface of the transition layer 3. The thickness of the single layer was controlled by adjusting the residence time of the substrate 1 in front of the AlCrTiNi and CrNi targets. The bias voltage was -80 V, the power of the AlCrTiNi target was 6 kW, the power of the CrNi target was 8 kW, the deposition temperature was 180°C, and the deposition time was 260 min.
[0086] Step 6: Ni-CrC-DLC coating 5:
[0087] A CrNi target is used as the target material, a carbon-containing gas source is used as the working gas, argon is used as the auxiliary gas, magnetron sputtering technology is adopted, and the ion source is turned on at the same time. The vacuum chamber pressure is 0.5Pa, the bias voltage is -70V, the target power is 5kW, the deposition temperature is 150℃, and the deposition time is 60min. After the deposition is completed, the sputtering target is turned off, the substrate bias is stopped, the gas is stopped, and the vacuum is continued. The workpiece is cooled to below 80℃ with the furnace, the vacuum chamber is opened, the workpiece is taken out, and the coating process is completed.
[0088] The total thickness of the obtained multi-layer composite coating is 16.6 microns; the nanohardness is 22 GPa; and the friction coefficient with the GCr15 steel ball is 0.15.
[0089] Example 4
[0090] In this embodiment, the ultra-thick composite coating with the multi-layer structure is prepared on the surface of a 304 stainless steel sample. The specific process steps are as follows:
[0091] Step 1: Pre-cleaning of workpiece:
[0092] After grinding and polishing, the workpiece / sample surface is ultrasonicated in anhydrous alcohol solution for 22 minutes, then blown dry with dry nitrogen and placed on the workpiece holder in the vacuum chamber to wait for coating;
[0093] Step 2: Ion etching and cleaning:
[0094] The sample treated in step 1 was placed in the vacuum chamber of the magnetron sputtering coating machine and evacuated to a vacuum better than 5×10 - 3 Pa; turn on the ion source, introduce high-purity argon gas, adjust the gas pressure to 0.40Pa, apply a negative bias voltage to the substrate 1, and etch and clean the substrate 1 at a bias voltage of -200V to remove impurities such as oxides and contamination layers attached to the surface. The etching time is 35min;
[0095] Step 3: Deposition of Cr bonding layer:
[0096] A high-purity chromium target with a purity of 99.9% was used. After ion etching was completed, the argon gas pressure was adjusted to 0.65 Pa. The magnetron sputtering chromium target was turned on to deposit the bonding layer 2 on the substrate surface. The bias voltage was -70 V, the target power was 6 kW, the deposition temperature was 300°C, and the deposition time was 90 min.
[0097] Step 4: Deposition of CrN / CrCN double-layer transition layer 3:
[0098] The N2 gas is introduced, the ratio of argon flow rate to nitrogen flow rate is adjusted to 1:5, the vacuum chamber gas pressure is adjusted to 0.6 Pa, the bias voltage and the target power are unchanged, a CrN layer is deposited on the surface of the adhesive layer 2 by using a magnetron sputtering technology, and the deposition time is 90 minutes; then the C2H2 gas is introduced, the ratio of argon to nitrogen and C2H2 total flow rate is adjusted to 1:4, the bias voltage and the target power are unchanged, a CrCN layer is deposited on the surface of the CrN layer by using a magnetron sputtering technology, and the deposition time is 90 minutes;
[0099] Step five: plating AlCrTiNiCN / CrNiCN alternating stack 4:
[0100] The AlCrTiNi target and the CrNi target are used as target materials, the N2 gas and the C2H2 are used as working gases, and the argon is used as an auxiliary gas; the vacuum chamber gas pressure is adjusted to 0.7 Pa; the AlCrTiNiCN layer and the CrNiCN layer are deposited on the surface of the transition layer 3 by using a magnetron sputtering technology; the single-layer thickness is controlled by adjusting the residence time of the substrate 1 in front of the AlCrTiNi target and the CrNi target; the bias voltage is -100 V; the AlCrTiNi target power is 8 kW; the CrNi target power is 7 kW; the deposition temperature is 300 DEG C; and the deposition time is 300 min.
[0101] Step six: plating Ni-CrC-DLC surface layer 5:
[0102] The CrNi target is used as a target material, the carbon-containing gas source is used as a working gas, and the argon is used as an auxiliary gas; a magnetron sputtering technology is used; the ion source is started at the same time; the vacuum chamber gas pressure is 0.65 Pa; the bias voltage is -90 V; the target power is 7 kW; the deposition temperature is 300 DEG C; the deposition time is 60 min; after the deposition is completed, the sputtering target material is turned off, the pulse negative bias voltage of the substrate 1 is stopped, and the gas is stopped; the vacuum is continued to be pumped; the workpiece is cooled to below 80 DEG C in the furnace; the vacuum chamber is opened; the workpiece is taken out; and the plating process is completed.
[0103] The total thickness of the obtained multilayer composite coating is 13.4 microns; the nano-hardness is 17 GPa; and the friction coefficient with the GCr15 steel ball is 0.19.
[0104] As shown in FIG. 1, the multilayer structure of the composite coating deposited in this embodiment includes a substrate 1, an adhesive layer 2, an AlCrTiNiCN / CrNiCN alternating stack 4, and a Ni-CrC-DLC surface layer 5. Figure 1 FIG. 1 is a schematic diagram of the three-dimensional structure of the multilayer structure of the composite coating deposited in this embodiment.
[0105] As shown in FIG. 2, the multilayer structure of the composite coating deposited in this embodiment includes a substrate 1, an adhesive layer 2, an AlCrTiNiCN / CrNiCN alternating stack 4, and a Ni-CrC-DLC surface layer 5. Figure 2 FIG. 2 is a schematic diagram of the cross-sectional structure of the multilayer structure of the composite coating deposited in this embodiment.
[0106] As shown in FIG. 3, the multilayer structure of the composite coating deposited in this embodiment includes a substrate 1, an adhesive layer 2, an AlCrTiNiCN / CrNiCN alternating stack 4, and a Ni-CrC-DLC surface layer 5. Figure 3 FIG. 3 is a friction coefficient change curve of the multilayer structure of the composite coating deposited in this embodiment 1. It can be seen that the coating has a relatively low friction coefficient, and the average is 0.18.
Claims
1. A multi-layered ultra-thick composite coating comprising a substrate (1); characterized in that: The invention also includes a bonding layer (2), a transition layer (2), an alternating laminate (4) and a surface layer (5); the outer surface of the substrate (1) is provided with a bonding layer (2) composed of a Cr layer, the outer surface of the bonding layer (2) is provided with a transition layer (3) composed of a CrN / CrCN double layer, the outer surface of the transition layer (3) is provided with an alternating laminate (4) composed of alternately deposited AlCrTiNiCN / CrNiCN, and the outer surface of the alternating laminate (4) is provided with a surface layer (5) composed of Ni-CrC-DLC.
2. The ultra-thick composite coating of the multi-layer structure according to claim 1, characterized in that: The thickness of the bonding layer (2) is 0.2 to 2 μm; the thickness of the transition layer (3) is 0.5 to 5 μm; the thickness of the alternating laminate (4) is 2 to 30 μm; the alternating laminate (4) comprises two or more alternating laminate periodic layers, wherein each alternating laminate periodic layer comprises a layer of AlCrTiNiCN and a layer of CrNiCN; the thickness of the surface layer (5) is 0.5 to 5 μm; and the total thickness of the multi-layer structure ultra-thick composite coating is 4 to 40 μm.
3. The ultra-thick composite coating of the multi-layer structure according to claim 2, characterized in that: The ultra-thick composite coating can be used in the field of surface protection of metal moving parts in harsh environments.
4. A method for preparing a multi-layer ultra-thick composite coating, characterized in that The invention comprises a multi-layer ultra-thick composite coating according to claim 3, characterized in that magnetron sputtering technology and ion source assisted magnetron sputtering technology are used to deposit alternating stacking layers (4) and surface layers (5) on the surfaces of the bonding layer (2) and the transition layer (3) to form a multi-layer ultra-thick composite coating.
5. A method for preparing a multi-layer ultra-thick composite coating, characterized in that The invention comprises a multi-layer ultra-thick composite coating according to claim 3, characterized in that arc ion plating technology and ion source assisted arc ion plating technology are used to deposit alternating stacking layers (4) and surface layers (5) on the surfaces of the bonding layer (2) and the transition layer (3) to form a multi-layer ultra-thick composite coating.
6. The method for preparing a multi-layer ultra-thick composite coating according to claim 4, characterized in that: The specific steps are as follows: Step 1: Pre-cleaning of workpiece: After grinding and polishing, the workpiece surface is ultrasonically placed in anhydrous alcohol solution for 10 to 20 minutes, then dried with hot air and placed on the workpiece rack in the vacuum chamber to wait for coating; Step 2: Plating Cr bonding layer (2): A high-purity chromium target is used, an inert gas is used as a working atmosphere, and a magnetron sputtering technique is used to deposit a bonding layer (2) on the surface of a substrate (1), wherein the bias voltage is -20 to -100 V, the target power is 2 to 8 kW, the vacuum chamber pressure is 0.3 to 1.0 Pa, the deposition temperature is 100 to 350° C., and the deposition time is 10 to 90 minutes. Step 3: Plating CrN / CrCN transition layer (3): A Cr target is used as a target material and N2 gas is used as a working gas, and a magnetron sputtering technology is used to deposit a CrN layer on the surface of the bonding layer (2), wherein the bias voltage is -20 to -150 V, the target power is 2 to 8 kW, the vacuum chamber pressure is 0.3 to 1.0 Pa, the deposition temperature is 100 to 350° C., and the deposition time is 20 to 100 minutes; then a mixed gas of inert gas, N2 gas and carbon source gas is introduced, the vacuum chamber pressure is 0.3 to 1.0 Pa, the bias voltage is -20 to -150 V, the target power is 2 to 8 kW, the deposition temperature is 100 to 350° C., and the deposition time is 20 to 100 minutes; Step 4: Plating AlCrTiNiCN / CrNiCN alternating layers (4): AlCrTiNi target and CrNi target are used as target materials, N2 gas and carbon-containing gas source are used as working gas, and inert gas is used as auxiliary gas. AlCrTiNiCN layer and CrNiCN layer are alternately deposited on the surface of transition layer (3) by magnetron sputtering technology, wherein the bias voltage is -20 to -150V, the target power is 2 to 8kW, the vacuum chamber pressure is 0.3 to 1.0Pa, the deposition temperature is 100 to 350°C, and the deposition time is 30 to 360min. Step 5: Ni-CrC-DLC surface coating (5): Cr target and Ni target are used as target materials, carbon-containing gas source is used as working gas, inert gas is used as auxiliary gas, magnetron sputtering technology is adopted, and the ion source is turned on at the same time. The vacuum chamber pressure is 0.3~1.0Pa, the bias voltage is -20~-150V, the target power is 2~8kW, the deposition temperature is 100~350℃, and the deposition time is 20~100min.
7. The method for preparing a multi-layer ultra-thick composite coating according to claim 5, characterized in that: The specific steps are as follows: Step 1: Pre-cleaning of workpiece: After grinding and polishing, the workpiece surface is ultrasonically placed in anhydrous alcohol solution for 10 to 20 minutes, then dried with hot air and placed on the workpiece rack in the vacuum chamber to wait for coating; Step 2: Plating Cr bonding layer (2): A high-purity chromium target is used, an inert gas is used as a working atmosphere, and an arc ion plating technique is used to deposit a bonding layer (2) on the surface of a substrate (1), wherein the bias voltage is -30 to -200 V, the target arc current is 80 to 200 A, the vacuum chamber pressure is 0.5 to 2.0 Pa, the deposition temperature is 100 to 350° C., and the deposition time is 5 to 50 minutes. Step 3: Plating CrN / CrCN transition layer (3): A Cr target is used as a target material, N2 gas is used as a working gas, and an arc ion plating technology is used to deposit a CrN layer on the surface of the bonding layer (2), wherein the bias voltage is -40 to -200 V, the target arc current is 80 to 200 A, the vacuum chamber pressure is 1.0 to 3.0 Pa, the deposition temperature is 100 to 350° C., and the deposition time is 10 to 50 minutes; then a mixed gas of inert gas, N2 gas and carbon source gas is introduced, the vacuum chamber pressure is 1.0 to 3.0 Pa, the bias voltage is -40 to -200 V, the target arc current is 80 to 200 A, the deposition temperature is 100 to 350° C., and the deposition time is 10 to 50 minutes; Step 4: Plating AlCrTiNiCN / CrNiCN alternating layers (4): Using AlCrTiNi target and CrNi target as target materials, N2 gas and carbon-containing gas source as working gas, inert gas as auxiliary gas, and arc ion plating technology to deposit AlCrTiNiCN layer and CrNiCN layer on the surface of transition layer (3), wherein the bias voltage is -40 to -200V, the target arc current is 80 to 200A, the vacuum chamber pressure is 1.0 to 3.0Pa, the bias voltage is -40 to -300V, the deposition temperature is 100 to 350°C, and the deposition time is 20 to 240min; Step 5: Ni-CrC-DLC surface coating (5): Cr and Ni targets are used as target materials, carbon-containing gas source is used as working gas, inert gas is used as auxiliary gas, arc ion plating technology is adopted, the ion source is turned on at the same time, the vacuum chamber pressure is 1.0~3.0Pa, the bias voltage is -40~-300V, the target arc current is 80~200A, the deposition temperature is 100~350℃, and the deposition time is 10~50min.
8. The method for preparing a multi-layer ultra-thick composite coating according to any one of claims 6 to 7, characterized in that: The carbon source gas includes C2H2 and / or CH4; the inert gas atmosphere includes Ar atmosphere.